The antimicrobial activity of lapachol and its thiosemicarbazone and semicarbazone derivatives - Marina Azevêdo Souza; Susana Johann; Luciana Alves Rodrigues dos Santos Lima; Fernanda Fraga Campos; Isolda Castro Mendes; Heloisa Beraldo; Elaine Maria de Souza-Fagundes; Patrícia Silva Cisalpino; Carlos Augusto Rosa; Tânia Maria de Almeida Alves; Nívea Pereira de Sá; Carlos Leomar Zani (Memorias do Instituto Oswaldo Cruz, 2013)
Lapachol was chemically modified to obtain its thiosemicarbazone and semicarbazone derivatives. These compounds were tested for antimicrobial activity against several bacteria and fungi by the broth microdilution method. The thiosemicarbazone and semicarbazone derivatives of lapachol exhibited antimicrobial activity against the bacteria Enterococcus faecalis and Staphylococcus aureus with minimal inhibitory concentrations (MICs) of 0.05 and 0.10 µmol/mL, respectively. The thiosemicarbazone and semicarbazone derivatives were also active against the pathogenic yeast Cryptococcus gattii (MICs of 0.10 and 0.20 µmol/mL, respectively). In addition, the lapachol thiosemicarbazone derivative was active against 11 clinical isolates of Paracoccidioides brasiliensis, with MICs ranging from 0.01-0.10 µmol/mL. The lapachol-derived thiosemicarbazone was not cytotoxic to normal cells at the concentrations that were active against fungi and bacteria. We synthesised, for the first time, thiosemicarbazone and semicarbazone derivatives of lapachol. The MICs for the lapachol-derived thiosemicarbazone against S. aureus, E. faecalis, C. gattii and several isolates of P. brasiliensis indicated that this compound has the potential to be developed into novel drugs to treat infections caused these microbes.